Advances in comprehensive management and nursing of chronic graft-versus-host disease under the background of interferon-α therapy in the prevention of relapsed patients with acute myeloid leukemia after allogeneic hematopoietic stem cell transplantation (干扰素-α预防急性髓系白血病患者移植后复发背景下慢性移植物抗宿主病的综合管理与护理进展) - DONG Jian (董简); QIAN Huijun (钱慧军); LIU Qian (柳倩); WU Qiankun (吴千堃); MENG Ting (孟婷); WANG Xu (王旭); HE Hui (贺辉) (中西医结合护理)
Interferon-α therapy shows efficacy in reducing recurrence rate in patients with acute myeloid leukemia (AML) after allogeneic hematopoietic stem cell transplantation (allo-HSCT). However, it may increase the risk of chronic graft-versus-host disease (cGVHD) and related mortality, limiting the long-term efficacy of transplantation. This paper reviewed researches on comprehensive treatment and nursing of cGVHD under the background of interferon-α therapy in the prevention of relapsed patients with AML after allo-HSCT, and provided reference for the a precise intervention model that takes into account both the anti-leukemia effect and the management of long-term complications (干扰素-α抢先治疗在降低急性髓系白血病(AML)移植后复发率的同时, 也增加了慢性移植物抗宿主病(cGVHD)的发生率及其相关病死率, 是限制移植远期疗效的关键瓶颈。本研究综述了抢先应用干扰素-α预防AML复发背景下患者发生cGVHD的治疗与护理进展, 旨在为临床构建兼顾抗白血病效应与远期并发症管理的精准干预模式提供决策依据。)